Electroexcitation of giant resonances in ⁵⁴Fe and ⁵⁶Fe nuclei - Khvastunov, V.M.; Denyak, V.V.; Ranyuk, Yu.N. (Вопросы атомной науки и техники, 2004)
The investigation of giant multipole resonanсes in ⁵⁴Fe and ⁵⁶Fe nuclei has been carried out. The resonance at excitation energy of~13 MeV (51A¹/³) is shown to be of E2 type and to exist in both nuclei. In both nuclei the contribution of the E3 multipole is very small, especially of the 1 -ω branch of isovector resonance, and the E4 resonance is absent completely. Small E5 strength contribution is observed in both nuclei at excitation energy of 10 to 15 MeV. Досліджено мультипольні гігантські резонанси у ядрах 54Fe і ⁵⁶Fе. Отримано, що резонанс при енергії ~13 МеВ (51А-¹/³) є Е2 переходом і існує в обох ядрах. В обох ядрах внесок E3 переходів дуже малий, особливо 1 -ω гілки ізовекторного резонансу, а Е4 переходи взагалі відсутні. Це дуже відрізняє ⁵⁴Fe і ⁵⁶Fe від найближчих досліджених сусідів ⁵⁸Ni і ⁶⁵Cu . В обох ядрах виявлено невеликий внесок E5 сили при енергіях збудження 10…15 МеВ. Исследованы мультипольные гигантские резонансы в ядрах ⁵⁴Fe и ⁵⁶Fe. Получено, что резонанс при энергии ~13 МэВ (51А-¹/³) является E2 переходом и существует в обоих ядрах. В обоих ядрах вклад E3 переходов очень мал, особенно 1 -ω ветви изовекторного резонанса, а E4 переходы вообще отсутствуют. Это сильно отличает ⁵⁴Fe и ⁵⁶Fe от ближайших исследованных соседей ⁵⁸Ni и ⁶⁵Cu. В обоих ядрах обнаружен небольшой вклад Е5 силы в области энергий возбуждения 10…15 МэВ.